Epidemiological and Clinical Features of Severe Fever with Thrombocytopenia Syndrome in Japan, 2013–2014 - Kato, Hirofumi; Yamagishi, Takuya; Shimada, Tomoe; Matsui, Tamano; Shimojima, Masayuki; Saijo, Masayuki; Oishi, Kazunori (PloS one, 2016)
Although severe fever with thrombocytopenia syndrome (SFTS) was first reported from Japan in 2013, the precise clinical features and the risk factors for SFTS have not been fully investigated in Japan. Ninety-six cases of severe fever with thrombocytopenia syndrome (SFTS) were notified through the national surveillance system between April 2013 and September 2014 in Japan. All cases were from western Japan, and 82 cases (85%) had an onset between April and August. A retrospective observational study of the notified SFTS cases was conducted to identify the clinical features and laboratory findings during the same period. Of 96 notified cases, 49 (51%) were included in this study. Most case-patients were of advanced age (median age 78 years) and were retired or unemployed, or farmers. These case-patients had a history of outdoor activity within 2 weeks before the onset of illness. The median serum C-reactive protein concentration was slightly elevated at admission. Fungal infections such as invasive aspergilosis were found in 10% of these case-patients. Hemophagocytosis was observed in 15 of the 18 case-patients (83%) whose bone marrow samples were available. Fifteen cases were fatal, giving a case-fatality proportion of 31%. The proportion of neurological abnormalities and serum concentrations of lactate dehydrogenase and aspartate aminotransferase were significantly higher in the fatal cases than in the nonfatal cases during hospitalization. Appearance of neurological abnormality may be useful for predicting the prognosis in SFTS patients.